2020
DOI: 10.1111/dar.13084
|View full text |Cite
|
Sign up to set email alerts
|

Normalisation of non‐drinking? 15–16‐year‐olds' accounts of refraining from alcohol

Abstract: Introduction and Aims In many countries, adolescents' drinking has decreased substantially over recent years. This study aims to explore Norwegian adolescents' accounts of refraining from drinking alcohol and how their explanations are contextualised. Design and Methods Semi‐structured qualitative interviews were conducted with 95 adolescents aged 15–16 years (50 females), recruited from six schools in Norway. Interviews examined perceptions and experience of alcohol use, and how non‐drinking was reasoned for.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 33 publications
4
19
0
1
Order By: Relevance
“…Our results echo those of two recent qualitative studies from Norway [27] and Sweden [28] that also concluded that the cultural position of alcohol has changed among adolescents. The qualitative findings suggest that alcohol has lost its importance in socializing situations between peers and that today's adolescents do not perceive any peer pressure to drink [28] which is also supported by quantitative findings of drinking motives among Swedish youth [29].…”
Section: Discussionsupporting
confidence: 90%
“…Our results echo those of two recent qualitative studies from Norway [27] and Sweden [28] that also concluded that the cultural position of alcohol has changed among adolescents. The qualitative findings suggest that alcohol has lost its importance in socializing situations between peers and that today's adolescents do not perceive any peer pressure to drink [28] which is also supported by quantitative findings of drinking motives among Swedish youth [29].…”
Section: Discussionsupporting
confidence: 90%
“…We found that the time spent on homework increased and that school misconduct decreased, and that these changes also contributed to explain the drop in drinking to intoxication. This fits well with a recent finding that a stronger emphasis on academic performance is not compatible with heavy alcohol consumption and frequent drinking to intoxication [32]. Hegna et al [34] noted that the 'educational explosion' over the past few decades has left fewer options for those who do not complete senior high school, and it has been claimed that this has led to a more 'conformist' youth generation [35].…”
Section: Discussionsupporting
confidence: 87%
“…Parents' knowledge about their adolescent offspring's whereabouts has increased, and alcohol-specific parenting practices have become more restrictive [6,[11][12][13]. At least in the Nordic countries, it seems that young people want to perform better at school than previously, with higher academic ambitions [8,32], which fits our findings of more school conscientiousness. Finally, and well in line with the above-mentioned changes in young people's lives, delinquency and other risk-taking behaviours have declined in several countries [8,10,30,31], as we also found.…”
Section: Discussionsupporting
confidence: 75%
“…Fry, 2010;Lindsay, 2009), may be becoming a significant and avoidable risk for young people (e.g. Scheffels et al, 2020).…”
Section: Discussionmentioning
confidence: 99%